Is it true that there is a constant such that, if is a polynomial of degree 1999, then ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The key observation :
Consider the complexe plane, η > ε > 0 and z 0 ∈ C . Then, ∣ α − z 0 ∣ ≥ η in f ( ∣ z − z 0 ∣ ≤ ε min ∣ ∣ ∣ ∣ α z − α ∣ ∣ ∣ ∣ ) = C ( z 0 , η , ε ) > 0
Proof the observation
Indeed, if ∣ α − z 0 ∣ ≫ 1 , then ∣ z − z 0 ∣ ≤ ε min ∣ ∣ ∣ ∣ α z − α ∣ ∣ ∣ ∣ ≈ 1 ≥ 1 / 2 . Therefore we are bring back to a compact set : η ≤ ∣ α − z 0 ∣ ≤ R for some R > η (we call this compact set K ).
But because α ⟼ ∣ z − z 0 ∣ ≤ ε min ∣ ∣ ∣ ∣ α z − α ∣ ∣ ∣ ∣ is continuous, on the compact set K , it is bounded and reaches its bounds. Now observes that for every α ∈ K , ∣ z − z 0 ∣ ≤ ε min ∣ ∣ ∣ ∣ α z − α ∣ ∣ ∣ ∣ > 0 (In fact ≥ R η − ε )
Therefore, α ∈ K in f ( ∣ z − z 0 ∣ ≤ ε min ∣ ∣ ∣ ∣ α z − α ∣ ∣ ∣ ∣ ) = α ∈ K min ( ∣ z − z 0 ∣ ≤ ε min ∣ ∣ ∣ ∣ α z − α ∣ ∣ ∣ ∣ ) > 0
Which ends the proof of the observation.
Remark : the denpence on z 0 is hidden in R .
\
Now we are ready to answer our problem. Let P polynomial of degree 1999.
Without loss of generality (by homogeneity), we can suppose P ( 0 ) = 1 .
Therefore P = k = 1 ∏ 1 9 9 9 α k X − α k where the α k 's are the complexe roots of P .
Consider 2000 following disks : B ( − 1 + 2 0 0 0 2 k − 1 , 2 0 0 0 1 ) for k = 1 , 2 , ⋯ , 2 0 0 0 . Where B ( z , r ) is the disk center at z with radius r . The disks are disjoint and there are only 1999 roots so, at least one of them does not contain a root (let's say the m t h ball). Call it center z m and apply the key observation with ε = 8 0 0 0 1 and η = 4 0 0 0 1 :
∣ P ( x ) ∣ ≥ C ( z m , 4 0 0 0 1 , 8 0 0 0 1 ) 1 9 9 9 ∀ x ∈ [ z m − 8 0 0 0 1 , z m + 8 0 0 0 1 ]
So, ∣ P ( x ) ∣ ≥ h = 1 , 2 , ⋯ , 2 0 0 0 min C ( z h , 4 0 0 0 1 , 8 0 0 0 1 ) 1 9 9 9 = Q ( 4 0 0 0 1 , 8 0 0 0 1 ) 1 9 9 9 > 0 ∀ x ∈ [ z m − 8 0 0 0 1 , z m + 8 0 0 0 1 ]
Now, Q ( 4 0 0 0 1 , 8 0 0 0 1 ) 1 9 9 9 = : R 1 9 9 9 no more depends on P at all.
Finally, ∫ − 1 1 ∣ P ∣ ≥ ∫ z m − 8 0 0 0 1 z m + 8 0 0 0 1 ∣ P ∣ ≥ 4 0 0 0 R 1 9 9 9 > 0
So, ∣ P ( 0 ) ∣ = 1 ≤ R 1 9 9 9 4 0 0 0 ∫ − 1 1 ∣ P ∣